RNA-Binding Protein COL14A1, TNS1, NUSAP1 and YWHAE Are Valid Biomarkers to Predict Peritoneal Metastasis in Gastric Cancer - Jiang, Yue; Chen, Fangfang; Ren, Xunshan; Yang, Yu; Luo, Jiajun; Yuan, Jingwen; Yuan, Jingping; Tong, Qiang (Frontiers in Oncology, 2022)
Gastric cancer (GC) is the third leading cause of tumor related mortality worldwide. Peritoneal metastasis (PM) occurs in more than half of advanced GC patients, leading to poor prognosis. Therefore, the GSE62254 cohort was used to construct a signature consisting of four RNA-binding proteins (RBP) to predict the possibility of PM in GC patients. Then, ROC curves were plotted followed by calculation of AUCs, showing that the signature had a similar predictive accuracy compared with the TNM staging system. Importantly, the capability of prediction was enhanced by combining the classifier and TNM staging. In order to validate the expression of the four RBPs in GC tissues with and without PM, immunohistochemistry was further performed on samples from 108 patients. The differential expression of COL14A1, TNS1, NUSAP1 and YWHAE was in accordance with the emergence of PM. Afterwards, we produced Kaplan–Meier curves according to the signature and differential expression of the RBPs in patients. Finally, CCK-8 assays were performed to verify the effect on cell proliferation, finding that COL14A1 and TNS1 promoted cell proliferation, while NUSAP1 and YWHAE led to suppressed cell proliferation. In conclusion, the four-RBP-based signature, combined with TNM staging, has the potential to predict risk of PM in GC.